3D Printing for Sustainable Construction - Tay, Daniel Yi Wei (CRC Press, Taylor & Francis Group, 2021)
Sustainability is interpreted as the effective use of resources as well as the preservation of the environment. A sustainable building is giving back to the environment more than it takes and ensuring that the resources is being used in an effective way that would benefit the community. A combination of smart design, efficient technology and designing buildings with sustainability in mind from the start of the designing phase is therefore necessary. 3D concrete printing can be a sustainable solution because of its ability to manufacture complex shapes to enable passive design thus reducing energy consumption. This article presents an overview on the sustainability of 3D concrete printing in terms of printable green materials as well as sustainable architectural design to achieve passive system.